2020
DOI: 10.1007/s10903-020-01015-4
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Willingness to Participate in Research Based on Study Risk Level Among a Community Sample of African Americans in North Central Florida

Abstract: This study examined the association between sex, study risks and willingness to participate in research among a community sample of African Americans. We hypothesized that African American males would be more willing to participate in studies involving both minimal and greater-than-minimal risk. The study sample was recruited through a community engagement program (HealthStreet). Interviewers obtained information on socio-demographic variables and willingness to participate in various research types. We catego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 49 publications
5
26
0
Order By: Relevance
“…Secondly, we noted that approximately 72% of respondents were women. This may be consistent with previous studies that identified that women are more likely than men to participate in research or survey studies 34 . Although this may cause concern for generalizability of the results, the gender distribution may also be driven by the healthcare setting; the US Census Bureau estimates that 76% of healthcare employees are women which is consistent with the gender distribution observed in this study 35 .…”
Section: Discussionsupporting
confidence: 91%
“…Secondly, we noted that approximately 72% of respondents were women. This may be consistent with previous studies that identified that women are more likely than men to participate in research or survey studies 34 . Although this may cause concern for generalizability of the results, the gender distribution may also be driven by the healthcare setting; the US Census Bureau estimates that 76% of healthcare employees are women which is consistent with the gender distribution observed in this study 35 .…”
Section: Discussionsupporting
confidence: 91%
“…Yet the proportion of research (i.e., 50) we identified that had been conducted within the last decade is still not ideal when considering the international evidence suggesting an increase in internalising and externalising problems in CYP in the twenty-first century [ 141 ]. Our findings also add to the mixed views on sex differences on willingness to participate in research (e.g., [ 142 ]) by suggesting slightly more research activity among females when compared to males. However, this is still an understudied area in the CYP literature and may also indicate the influence of culture on the participants’ perception of research which could influence their decision to participate.…”
Section: Discussionsupporting
confidence: 74%
“…In general, in health (behaviour) research, males are less likely to participate [ 31 ]. Reasons for lower participation among males are that they were generally less interested in participating than females, and that they were more likely to decline research participation due to time constraints [ 32 ]. Ryan et al found that response rate among males improved substantially through the use of targeted Facebook advertising, incorporating features such as using images of men that appealed to leadership themes and using concise text [ 33 ].…”
Section: Discussionmentioning
confidence: 99%